The Econometrics of Agricultural Supply: An Application to the World Coffee Market - Wickens, M. R.; Greenfield, J. N. (The Review of Economics and Statistics, 1973)
T HE importance of the dynamic structure of agricultural supply functions has been recognised for a long time. The seminal work of Nerlove 1 has offered an elegant solution to this problem which has been so widely adopted that at present it might even be regarded as the standard approach. The impact of Nerlove's work on dynamic models has been felt far beyond agricultural economics and in the course of this diffusion, a number of modifications have been proposed. Two of the main criticisms concern the ad hoc nature of the model and the fact that the dynamic has been added to a static optimising model.2 A more satisfactory formulation would be to specify an objective function in which adjustment and other dynamic costs are included and to optimise this, perhaps over a planning horizon. Developments along these lines are occurring in several fields: for example, investment and labour theory.3 Surprisingly, perhaps, they have not happened in agricultural economics, the area where some of the early advances in dynamics were made. The supply of tree crops is particularly suited to this treatment as there are long lags of gestation between planting and cropping. The investment decision of planting trees is a classical problem in capital theory. The harvesting decision and the decision to supply final markets, especially where they are foreign markets, introduces further lags. Moreover, many of the intractable problems of capital theory are simplified where the main source of capital is trees. One explanation for the absence of parallel development in the field of agricultural economics is that Nerlove's model was originally applied to field crops in which long lags are absent. The success of this model for field crops is, however, not a sufficient justification for its use for tree crops where long lags may be expected. In this paper an attempt is made to fill this gap by constructing a structural model of tree crop supply. The model is developed with reference to the supply of coffee in Brazil, for the sake of concreteness and ease of interpretation and because coffee is a crop possessing most of the characteristics outlined above.